61 The impact of frailty on in-hospital outcomes among patients undergoing percutaneous coronary intervention in the United States. (May 2019) - Kwok, Shing; Achenbach, Stephan; Curzen, Nick; Fischman, David; Savage, Michael; Bagur, Rodrigo; Kontopantelis, Evangelos; Martin, Glen; Steg, P Gabriel; Mamas, Mamas
Abstract : Introduction: The proportion of elderly patients who undergo percutaneous coronary intervention (PCI) is growing. There is increasing awareness that frailty, which is common in the elderly, may be an important marker of adverse outcomes. This study evaluates a national cohort of patients who underwent PCI regarding the prevalence of frailty, changes over time, and associated outcomes using a validated Hospital Frailty Risk Score (HFRS). Methods: We included adults who underwent PCI procedures between 2004 and 2014 in the National Inpatients Sample. Frailty risk was measured using a modified HFRS based on ICD-9 codes using the cutoffs <5, 5–15 and >15 for low, intermediate and high HFRS. Multiple logistic regressions were used to examine the associations between HFRS group and adverse outcomes after PCI. Results: There were 7, 306, 007 admissions for PCI and 94.58% had a low HFRS(<5), 5.39% had an intermediate HFRS(5–15) and 0.03% had a high HFRS(>15). Frailty increased over time as the prevalence of intermediate or high frailty risk was 1.9% in 2004 to 11.7% in 2014. Common variables contributing to frailty in the PCI cohort appear to be fluid and electrolyte disorder (8.43%), hypotension (4.15%), kidney disease (acute renal failure 5.29%, chronic renal failure 8.88%) and anaemia (5.33%). In-hospital death increased from 1.0% with low HFRS to 13.9% with HFRS and length of stay increased from 2.9 days to 17.1 days from low to high HFRS. A cost difference was observed depending on frailty which was 17, 743, 38, 824 and 56, 119 for low, intermediate and high HFRS, respectively. High frailty risk was independently associated with a significant increase in in-hospital death (OR 9.91 95%CI 7.17–13.71), bleeding complications (OR 4.99 95%CI 3.82–6.51) and vascular complications (OR 3.96 95%CI 3.00–5.23) as compared to patients with low risk of HFRS. Conclusion: Frailty is prevalent among patients who undergo PCI. There is a strikingly increased in frailty over time and those with high HFRS had a 10-fold increase in odds of mortality compared to low risk of frailty. Improved education and increased awareness of the impact of frailty could facilitate better tailored care to minimise risk of adverse outcomes and its associated costs in PCI. Conflict of Interest: None